How Have Emissions and Weather Patterns Contributed to Air Pollution in Lanzhou, China? - Yunfei Miao; Hongru Yan; Min Zhang (Atmosphere)
Air quality is predominantly influenced by two factors: emission sources and meteorological conditions. Understanding their relative contribution is essential for developing effective air pollution control strategies. Two rounds of lockdown measures in Lanzhou during the winter of 2021 and 2022 offered a valuable opportunity to reveal the impact of pollutant emissions and meteorological conditions on air pollution events. The reduction in emissions during the pandemic lockdown period (2021–2022) resulted in a 36.05% decrease in PM2.5 concentrations compared to the historical period of 2014–2020. Using ERA5 reanalysis meteorological data and principal component analysis, weather patterns were classified into three distinct types: favorable for pollutant accumulation (FPA), unfavorable for pollutant accumulation (NFP), and neutral condition (NTL). A comparative analysis of pollutant concentrations, frequency, and duration of each weather type during the lockdown and historical periods revealed that weather types had a minimal impact on pollutant levels, with emissions serving as the dominant factor. Nevertheless, the occurrence of FPA was often linked to severe pollution events, suggesting a positive feedback loop between severe pollution and FPA weather type. This indicated that FPA can lead to severe pollution events and more severe pollution may be associated with prolonged FPA durations. These findings suggest that identifying FPA weather patterns can significantly inform the implementation of air pollution control measures to mitigate air pollution levels.